(untitled) (Research, Society and Development, 2023)
Introduction: This study aims to analyze the importance of dental care for patients with disabilities. And specifically, describe the limitations given to patients with disabilities; identify how dental care occurs for individuals with PwD; and score the factors that show the importance and benefits of dental care for patients with disabilities. Methodology: The study is an Integrative Literature Review (RIL), which included scientific productions from 2017 to 2022 that were related to the theme and presented consistency during the research. Result: As a result, 13 articles were obtained from the bases: LILACS, SCIELO and Google Scholar. One of the most common challenges in caring for people with disabilities is understanding how to manage behavior during surgery or dental procedures, as the specifics of the patient’s disability need to be elucidated, considering their symptoms and aggressive behavior, involuntary movements or fears that make it difficult to sanitation. Results and discussions: Therefore, the importance of dental care for patients with disabilities was perceived, considering that the service aims to seek health promotion measures and preventive and therapeutic activities with regard to oral health care. Conclusion: It is worth noting that, in view of the literature review, it was possible to show that within the care of PwD there are numerous singularities to be considered, from the treatment model to the form of communication between the triad of professionals, family members and patients, so that, then, service works effectively.